2012
DOI: 10.1111/j.1468-2494.2012.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of skin penetration of antioxidants of varying lipophilicity

Abstract: Antioxidants play a vital role in protecting the skin from environmental distress. As the skin is constantly exposed to harmful UV radiation, endogenous antioxidants present in the superficial layers of the skin neutralize reactive oxygen species. Over time, antioxidants become depleted and loss their protective effect on the skin. Therefore, supplementing skin with topical antioxidant can help replenish this loss and fight the oxidative stress. The objective of this study was to deliver antioxidants topically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Keratinocytes are known to build a tight layer of cells that can be used as epidermal grafts (Fig. S2g) 37 , and these cells represent a prime target for lotions and emollients based on RSV 38,39 .…”
Section: Effects On Primary Human Keratinocytesmentioning
confidence: 99%
“…Keratinocytes are known to build a tight layer of cells that can be used as epidermal grafts (Fig. S2g) 37 , and these cells represent a prime target for lotions and emollients based on RSV 38,39 .…”
Section: Effects On Primary Human Keratinocytesmentioning
confidence: 99%
“…Since the endogenous antioxidant concentration decreases from the outermost to the deeper layers of the skin, natural antioxidants can be applied topically to protect skin from oxidative stress induced by UV radiation, although not all antioxidants have similar affinity for different layers of the skin (Abla and Banga, 2013). In order to confirm the potential of the extracts for topical use, irritability assays with the Episkin test were performed.…”
Section: Irritability Testsmentioning
confidence: 99%
“…While the skin penetration of trans-resveratrol and other antioxidants upon topical application have already been studied by authors such as Abla and Gamba [25], these investigations used pig ear skin as a model for human skin penetrability. The authors found that catechin showed the greatest accumulation in the stratum corneum, followed by trans-resveratrol and retinol.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, several attempts have been made to develop formulations to increase its skin penetration [24]. Abla and Banga [25] evaluated the penetration of antioxidants into pig-ear skin, and found decreasing concentrations of catechin, resveratrol and curcumin in the stratum corneum. Approximately 90% of the total amount of polyphenols in the skin was retained in the stratum corneum, with only 10% penetrating the underlying layers of skin.…”
mentioning
confidence: 99%